Determinação de Cd, Pb e Cu em particulados atmosféricos da região de Presidente Prudente por análise voltamétrica utilizando eletrodo de mercúrio - Proença, Camila dos Anjos [UNESP] (2014)
When considering the different forms of pollution in urban and industrial areas, the atmospheric particulate matter (MP) stands out thanks to its toxic potential and different chemical compositions. Toxic metals associated to MP are considered noxious to the health and to different species of the biota. Even though in the literature the studies that refer to the metal determination in MP are small, it of big significance knowing the flow deposition of these elements in order to indicate possible roots, predict effects due to its high toxicity and to allow in the future, establishing future Public Politic when it is displayed necessary, since these same ones doesn’t have well defined legislations. As a consequence, the present work has as objective the determination of Cd, Pb and Cu in atmospheric particulate matter in the city of Presidente Prudente, SP. The city of Presidente Prudente, SP has four small industrial districts have access to state highways and even national importance. In agricultural terms, the cultivation of sugar cane is harvested area of approximately 50.8%. The samples of particulate matter were collected in four areas of great automobile density and people circulation in the city these being: The Weather Station of the Faculty of Sciences and Technology of UNESP, in the bus terminal of the city of Presidente Prudente, in the 9 de Julho square and UBS Vila Real. 80 collected samples were studied for a term of fifteen days, term comprehended between March 27 of 2011 and April 03 of 2013. The quantification of the metals was done through the Voltammetric technique of differential pulses with anodic stripping using mercury electrode in the pendant droplet way. The optimized experimental parameters, sample volume and pre-concentration time were of 4,0 mL and 150s, respectively. For the determined elements, the decomposition method selected was with 65% nitric acid (v/v). The results were valued in relation to the ...